Cardiovascular safety of antimuscarinic add‐on therapy in patients with overactive bladder who had a suboptimal response to mirabegron monotherapy: A post hoc analysis from the Japanese MILAI II study. Issue 1 (30th September 2019) - Katoh, Takao; Igawa, Yasuhiko; Yamaguchi, Osamu; Kato, Daisuke; Hamada, Takuya; Kuroishi, Kentaro
Abstract: Objective: This analysis was conducted to investigate the cardiovascular (CV) safety outcomes from the MILAI II study. MILAI II was conducted to evaluate the long‐term safety and efficacy of antimuscarinic add‐on therapy to mirabegron over 52 weeks in patients with overactive bladder (OAB) symptoms. Methods: MILAI II consisted of a 2‐week screening period (patients received mirabegron 50 mg once daily) plus a 52‐week treatment period (patients were randomized to receive a combination of mirabegron 50 mg/d plus solifenacin 5 mg/d, propiverine 20 mg/d, imidafenacin 0.2 mg/d, or tolterodine 4 mg/d). CV safety was assessed using treatment‐emergent adverse events (TEAEs), vital signs, and 12‐lead electrocardiograms (ECGs). Vital signs and ECG data were evaluated for each patient using worst post‐baseline values reported. Results: Of 647 patients, 570 (88.1%) were female with a mean age of 65 years. CV history at baseline and CV‐related concomitant medication use throughout the study were balanced between groups. The incidences of overall and drug‐related CV TEAEs were ≤8.1% and ≤6.2%, respectively, for all groups. The most common TEAEs were ECG T wave amplitude decreased, ECG QT prolonged, and ventricular extrasystoles. Overall, 36 TEAEs of interest related to the CV system that were possibly/probably related to treatment were reported with similar incidences for each group. For the worst post‐baseline vital signs and ECGs, no relationships were noted in terms of either timing or treatment group. Conclusion: A favorable CV safety profile was observed following long‐term combination treatment with mirabegron and an antimuscarinic in patients with OAB symptoms.